100% oxygen mobilizes stem cells and up-regulates MIF and APRIL in humans: a new point on the hormetic dose curve - MacLaughlin, Kent J.; Barton, Gregory P.; MacLaughlin, Julia E.; Lamers, Jacob J.; Marcou, Matthew D.; O’Brien, Matthew J.; Braun, Rudolf K.; Eldridge, Marlowe W. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe aim of the current study was to test normobaric 100% oxygen (NBO) (PiO2 = 713 mmHg) for stem cell mobilization and cytokine modulation. Although current oxygen therapy (PiO2 = 1,473–2,233 mmHg) is well known to mobilize stem cells and modulate cytokine, little is known about NBO and its place on the low dose stimulation phase of the hormetic dose curve of oxygen. We asked the question, will NBO mobilize stem cells and modulate cytokines. A positive outcome presents the potential to create and refine oxygen treatment protocols, expand access, and optimize patient outcomes.MethodsHealthy 30–35-year-old volunteers were exposed to 100% normobaric oxygen for 60 min, M-F, for 10 exposures over 2 weeks. Venous blood samples were collected at four time points: 1) prior to the first exposure (serving as the control for each subject), 2) immediately after the first exposure (to measure the acute effect), 3) immediately before the ninth exposure (to measure the chronic effect), and 4) three days after the final exposure (to assess durability). Blinded scientists used flow cytometry to gate and quantify the Stem Progenitor Cells (SPCs).ResultsCD45dim/CD34+/CD133+ and CD45+/CD34+/CD133+ were significantly mobilized following nine daily one-hour exposures to normobaric 100% oxygen. Conversely CD45−/CD34+/CD133+, CD45-/CD34+/CD133− and CD45−/CD34−/CD133+ phenotypes were downregulated suggesting differentiation into more mature phenotypes. The CD133+ phenotype exhibited a maturing from CD45− to CD45dim stem cells. CD45−/CD34, CD45−/CD31 and CD45−/CD105 were downregulated with no changes in related CD45dim and CD45+ phenotypes. The cytokines “macrophage migration inhibitory factor” (MIF) and “a proliferation inducing ligand” (APRIL) were significantly upregulated.ConclusionThis study demonstrates that 100% normobaric oxygen mobilizes stem cells and upregulates the expression of the inflammatory cytokines marking a new point on the low dose stimulation phase of the hormetic dose curve of oxygen.